Acute dilated cardiomyopathy in the setting of catastrophic antiphospholipid syndrome and thrombotic microangiopathy: A case series and review. Issue 1 (31st July 2020) - Hermel, Melody; Hermel, David; Azam, Saif; Shinbane, Jerold; Sarcon, Annahita; Jones, Erika; Mehta, Arjun; Grazette, Luanda; Liebman, Howard; Weitz, Ilene
Abstract: Catastrophic antiphospholipid antibody syndrome (CAPS) is a rare form of antiphospholipid syndrome, an autoimmune condition characterized by vascular thromboses, pregnancy loss, and antiphospholipid (aPL) antibodies. Diagnosis of CAPS relies on thrombosis of at least three different organs systems over 1 week, histopathological evidence of small vessel occlusion, and high aPL antibody titers. In a subset of precipitating circumstances, activation or disruption of endothelial cells in the microvasculature may occur along with cardiomyopathy. We present two cases of CAPS‐associated dilated cardiomyopathy at our institution, focusing on disease management, pathophysiology, and treatment. These patients were of Southeastern Asian descent, raising the possibility of genetic polymorphisms contributing to the development of cardiomyopathy. Both met CAPS criteria and both demonstrated clinicopathologic thrombotic microangiopathy (TMA) and complement activation and developed severe dilated cardiomyopathy with shock. Complement activation plays an important role in the development of CAPS and may be important in the pathogenesis of CAPS‐associated cardiomyopathy. Clinical suspicion for TMA as a pathophysiologic mechanism of unexplained heart failure in CAPS is important and increased awareness of cardiac side effects is necessary so that early treatment can be initiated to halt further cardiac and systemic complications.